El ecuavoly como deporte tradicional para disminuir el sedentarismo en el Club 23 de Abril de la ciudad de Machala año 2013. - Fausto Penacho, Zambrano Serrano (2013)
In chapter one the definition of the problem, objective which will serve to find the necessary and relevant information to be able to develop the present work.